1968
DOI: 10.1111/j.1432-1033.1967.tb19562.x
|View full text |Cite
|
Sign up to set email alerts
|

A Collagenolytic Enzyme from Aspergillus oryzae

Abstract: 1.A highly purified protease has been prepared from culture filtrates of Aspergillus oqzae. The process consists of four steps, namely the dialysis of the starting material, precipitation with acetone, separation by carrier-free electrophoresis and fractionation with acetone. The specific activity of the protease is increased 40 times or more. The product was shown to be a single substance by means of the ultracentrifuge, disc electrophoresis and immuno-electrophoresis. As far as investigated, it is free of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1971
1971
1996
1996

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Moreover, lyophilization did not much affect the enzyme activity. These results were similar to those obtained with the alkaline proteinases detected in Aspergillus and Penicillium (1,3,5,7,11,13,14,16,18). The results obtained here will provide useful information for separating the enzymes.…”
Section: And Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, lyophilization did not much affect the enzyme activity. These results were similar to those obtained with the alkaline proteinases detected in Aspergillus and Penicillium (1,3,5,7,11,13,14,16,18). The results obtained here will provide useful information for separating the enzymes.…”
Section: And Discussionsupporting
confidence: 79%
“…Several strains of Aspergillus and Penicillium which are close relatives of Monascus are known to produce the serine-alkaline proteinases described above. Studies of the substrate specificities of some of them indicated that their specificities were quite different from chymotrypsin or trypsin (13,18). Since alkaline proteinases of Monascus were also considered to be serine proteinases, it will also be a subject of considerable interest to characterize them enzymologically and compare them with those of other origins.…”
Section: And Discussionmentioning
confidence: 99%
“…In all probability, it is a t this stage that the enzymes frequently encountered in animal tissues and capable of cleaving Z-GPGGPA, PZ-PLGPA, and other model pept,ides (see Section III.B.9) play their role in collagen metabolism. They may be peptidases in nature, even quite specific peptidases, but the same type of reaction can also be catalyzed by endopeptidases of poor specificity requirements (180).…”
Section: Mechanisms Suggested For Breakdown Of Collagen In Vivomentioning
confidence: 99%
“…The microorganisms synthesizing alkaline proteases include Aspergillus orycae [38,39], Aspergillus flavus [39], Streptococcus griseus [40] and Streptococcus faradiae [41]. Neutral proteases are synthesized, e.g., by Pseudomonas aeruginosa [38]. Mycobacter produces acid proteases [42].…”
Section: Protein Hydrolyzing Enzymesmentioning
confidence: 99%